Specialized heuristic algorithms for AC transmission expansion planning problem - Gutierrez, Jose Nicolas Melchor [UNESP]; Romero, Ruben A.; Mancarella, Pierluigi (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In recent years, AC power flow equations have been gaining relevance to represent the transmission planning problem. This trend will continue growing because of fast improvements of both computational resources and robust optimization techniques. Relevant problems associated with the voltage magnitude and reactive power may be difficult to represent in the transmission planning problem if the DC mathematical formulation is used instead of the AC formulation. However, the AC formulation remains difficult to solve even with the nowadays solution methodologies. Therefore, the development of new methods that allows to solve effectively the AC formulation are highly relevant. In this paper, novel heuristic methods to solve the transmission planning problem are proposed. The results show that the proposed heuristics for the AC transmission planning problem are both effective and efficient to solve the problem. Moreover, it has been determined the most suitable heuristic criteria for the proposed heuristics. The simulations are performed in the North Northeast Brazilian test system.
Keywords: AC formulation; Heuristic algorithm; Power system; Transmission planning